Issues in the implementation of 21st century learning skills in Malaysian ESL classrooms / Maizatulliza Muhamad and Goh Hock Seng - Muhamad, Maizatulliza; Goh, Hock Seng (Universiti Teknologi MARA, 2022)
Implementing 21st century learning skills in the English language classrooms requires both teachers and students to learn and adapt new knowledge and approaches during the teaching and learning process. This research seeks to identify the issues related to the implementation of 21st century learning skills in the Malaysian English as a Second Language (ESL) classrooms. Through semi-structured interviews and written surveys, this qualitative study involved five School Specialist Improvement Coaches (SISCs) and 116 English language teachers. The findings of the study highlighted important issues such as teachers' resistance and misconstrued perspectives towards 21st century learning skills. The results implicate that more comprehensive measures are needed to ensure effective implementation of 21st century learning skills in Malaysian ESL classrooms. The measures would assist in addressing issues which can hinder the implementation of 21st century learning skills.